Latent anaphylactic sensitisation of infants of low birth weight to cows' milk proteins. - Lucas, A (1984)
Latent systemic anaphylactic sensitisation to cows' milk was assessed in 61 preterm infants who were randomly assigned to receive either a special formula for preterm infants based on cows' milk or banked breast milk or one or other of these as a supplement to maternal milk. A single sample of venous blood was taken near to the time of discharge from the neonatal intensive care unit, and the histamine release by blood basophils in response to in vitro challenge with cows' milk and anti-IgE was measured. Compared with the blood from infants fed on human milk, that from infants fed on preterm formula showed a significant increase in histamine release to challenge with cows' milk, the response being greater in blood from infants of lower birth weight and gestational age. A smaller but significant increase in blood histamine release with anti-IgE challenge was observed in the group fed on preterm formula. Infants of low birth weight fed on preterm formula based on cows' milk may develop latent systemic sensitisation more rapidly than infants born at term. The clinical importance of this requires further investigation.